Posted by Tim on Saturday, March 29, 2008 at 4:41pm.
h(x)=5/x^2+6
I know the answer is: f(x)=x+6, g(x)=5/x^2, but I do not know how to get it. Can someone help me understand it?

Algebra  Anonymous, Saturday, March 29, 2008 at 5:42pm
First break it down
x=x+6 and x=5/x^2
x=1 x=2.5

Algebra  Damon, Saturday, March 29, 2008 at 6:03pm
You did not state the question.
Is it
h of f of g of x = 5/x^2 + 6 ?
There is surely more than one answer you can find by trial and error. For example another might be:
try g(x) = 1/x^2
then f(x) = 5 x
then f (g) = 5 (1/x^2) = 5/x^2 which is what I want except I have to add 6
so say h(x) = x + 6
then h (f) = 5/x^2 + 6
so the sequence
g(x) = 1/x^2
f(x) = 5 x
h(x) =x + 6
also yields
h(x) = 5/x^2 + 6

Algebra  TIm, Saturday, March 29, 2008 at 6:07pm
Consider the function h as defined. Find functions f and g so that
(f o g)(x)=h(x)
h(x)=5/x^2+6

Algebra  Damon, Saturday, March 29, 2008 at 6:32pm
oh
then I would modify that answer:
There is surely more than one answer you can find by trial and error. For example another might be:
try g(x) = 1/x^2
then f(x) = 5 x + 6
then f (g) = 5 (1/x^2) +6 = 5/x^2 + 6
then h (f) = 5/x^2 + 6
so the sequence
g(x) = 1/x^2
f(x) = 5 x + 6
also yields
h(x) = 5/x^2 + 6
Answer This Question
Related Questions
 Algebra  What is the Solution to 54/x = 6? A. X = 9 B. X = 6 C. X = 6 D. X...
 algebra  Solve the following equation: k2 + 4k = 0 By factoring and By using ...
 Algebra  Can someone check my algebra answers and help me with the problems I ...
 Maths algebra  Factorise the following: x^4  x^3  x^2 + x The answer is x(x+1...
 algebra  Is there a site or someone who can help me, im not getting the basic ...
 Algebra  I am having such a hard time in this class. Hopefully someone here can...
 algebra  In finding distance problems i understand the use of formula of d/rt ...
 algebra  Could someone please explain to me how to do this problem, and also ...
 Algebra  Can someone tell me if these problems have the right answers? I am ...
 algebra  the equation is :  (2x + 3)(4 + x). Using the distributive property...
More Related Questions